DERMAL CARCINOMA IN DOG AT ZOO CLINIC MAKASSAR - Andini, Nurul Sulfi; Monica, Wa Ode Santa; Deniaty, Sri; Wahyuni, Wahyuni; Gunawan, I Wayan Nico Fajar (Buletin Veteriner Udayana, 2023)
Dermal carcinoma or skin cancer in dog is a skin cancer consisting of various types of cancer which are included in it. The tumor appears as a solitary, non-encapsulated lump, generally hairless, and occasionally ulcerated, which moves freely. The diagnosis is generally made through microscopic examination of a sample of tumor cells (biopsy). Dermal carcinoma cases are cases that often occur in pets but reports of these cases are still rare especially in Indonesia. The purpose of writing is to describe clinical manifestations, clinical course, and case prognosis. This case report was obtained from the Zoo Clinic Makassar. A dog "Pororo" came with the owner with a temperature of 38.4 0 C, had an enlarged mass in the medial part of the radius dexter, encapsulated, with an estimated diameter of about 6 cm. Physical examination was carried out, followed by laboratory examination found that the WBC level was very high and anemia. Handling of cases in the form of removal of the tumor through surgery and followed by histopathological examination with Haematoxylin Eosin staining to determine tumor development stage, degree malignancy, prognosis and therapy. The results of histopathological examination stated that the cells found were not uniform and lead to metastasis. The diagnosis of Pororo disease is carcinoma dermatitis but the type is not clear because the primary cells have not been found. The prognosis is infausta, the presence of metastases worsens the prognosis of cases, and it is possible that new tumors will reappear after removal. Handling for similar cases should be done quickly and precisely so that the case prognosis can be better.